Adapting the Smoking Expectancy Scale for Adolescents (SESA) to Turkish Culture - Yazıcı, Hikmet; Camadan, Fatih; Kahveci, Gökhan (Addicta: The Turkish Journal on Addictions, 2017)
Different researchers have tried examining the results of expectations that affect people’s starting and continuing to smoke. These expectations can differ in terms of being a smoker, non-smoker, or ex-smoker. These expectations are also associated with age. So many scales have been developed in order to study the expectations of adults, youngsters, adolescents, and children about smoking. This study aims to adapt the Smoking Expectancy Scale for Adolescents (SESA) to Turkish culture. This scale has been adapted by basing itself on a study conducted over 720 university-level students with an average age of 17.5. The confirmatory factor analysis carried out in the investigation determined the SESA to have a 6-factor structure in Turkish. These factors are: affect control and boredom reduction, health costs and addiction, appearance-presentation costs, weight control, social benefits, and social costs. Additionally, the two dimensions of the scale, like the original scale, are seen as expected benefits and expected costs. As a result of the study, the scale is stated to have the quality of being able to measure adolescents’ expectations about smoking in terms of psychometric properties.Citation: Yazıcı, H., Camadan, F., & Kahveci, G. (2017). Adapting the Smoking Expectancy Scale for Adolescents (SESA) to Turkish culture. Addicta: The Turkish Journal on Addictions, 4, 207–220. http://dx.doi.org/10.15805/addicta.2017.4.2.0009
Keywords: Smoking; Expectancy; Adolescents; Adaptation; Scale